Pengembangan Media Kartu Soal Matematika Berbasis Google Sites Materi KPK dan FPB pada Siswa Kelas IV Sekolah Dasar - Evi Ananda Putri; Yulia Linguistika; Siti Mas'ula (Universitas Negeri Malang, 2022)
This development research aims to produce question card media based on google sites material for LCM and GCF grade IV Elementary Schools that are valid and interesting for students. The research model uses the ADDIE model with five stages of development including: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The product is a website link (https://sites.google.com/view/media-mathion-card/page-muka) which is online. Based on the validation results, the percentage of material experts is 85 percent (valid), the percentage of media experts is 96.67 percent (very valid), the percentage of teachers is 91.67 percent (very valid), and the student attractiveness test results are 93 percent (very good). So it was concluded that the mathion card media product was valid according to the experts and interesting for fourth grade students. Penelitian pengembangan ini bertujuan untuk menghasilkan media kartu soal berbasis google sites materi KPK dan FPB kelas IV Sekolah Dasar yang valid dan menarik bagi siswa. Model penelitian menggunakan model ADDIE dengan lima tahap pengembangan meliputi: (1) analisis, (2) desain, (3) pengembangan, (4) implementasi, dan (5) evaluasi. Produk berupa link website (https://sites.google.com/view/media-mathion-card/halaman-muka) yang secara online. Berdasarkan hasil validasi, persentase ahli materi 85 persen (valid), persentase ahli media 96,67 persen (sangat valid), persentase guru 91,67 persen (sangat valid), dan hasil uji kemenarikan siswa sebesar 93 persen (sangat baik). Sehingga disimpulkan bahwa produk media mathion card valid menurut para ahli serta menarik bagi siswa kelas IV.